Structural and Fractographic Analysis of Aluminum Alloy before and after Fatigue Loading - Uhricik, Milan; Palcek, Peter; Chalupova, Maria; Kucharikova, Lenka; Pastierovicova, Lucia; Medvecka, Denisa; Markovicova, Lenka; Balsianka, Robert; Vasko, Alan (Manufacturing Technology Journal, 2023)
The article deals with the analysis of the structure and fracture surface of aluminum alloy samples. Alu-minum alloy AlMg9 was used as an experimental material. The material from which the samples were made was supplied as cast without heat treatment, and specifically the material was produced by the continuous casting method. The structure of the test material was examined using a Neophot 32 optical microscope, and the fracture surface of the test sample was examined using a scanning electron microscope (SEM). The fatigue life of the aluminum alloy was tested by three-point bending cyclic loading using the parameters - frequency f = 100 Hz, temperature T = 22 ± 5 ℃ and stress ratio R = 0.11. The analysis showed that cast aluminum alloys are very sensitive to casting defects, such as porosity or the content and distribution of intermetallic phases. If large pores or phases are present on or near the surface of the sample, this can be the dominant cause of fatigue crack initiation and reduction of the fatigue lifetime.
Keywords: Aluminum Alloy; Fracture Surface; Structure; Fatigue; Bending Loading